Conhecimento e significado do cateterismo cardíaco para pacientes cardiopatas - Yana Thalita Barros de Oliveira Castro; Isaura Letícia Tavares Palmeira Rolim; Andréa Cristina Oliveira Silva; Líscia Divana Carvalho Silva (Universidade Federal do Ceará, 2016)
Objective: to describe the knowledge and significance of cardiac catheterization from cardiac patients' perspective. Methods: descriptive and qualitative study of patients undergoing cardiac catheterization. Five categories were identified through content analysis. Results: knowledge of patients on cardiac catheterization proved to be limited; the subject was surrounded by lack of knowledge. Cardiac catheterization means a treatment for unblocking coronary arteries and it is confused with therapeutic purposes. There were reports of symptoms related to heart disease such as fatigue and chest pain and related to the exams such as worry, anxiety, depression, fear and restlessness generated, mainly, by expectations of the unknown. The majority of the respondents proved to be satisfied with the results of the exam, due to the discovery and treatment of heart diseases. Conclusion: cardiac catheterization means treatment and clearance of coronary arteries and it is confused with therapeutic purposes. Feelings such as worry, anxiety, fear and restlessness are described when patients are subjected to examination, generated mainly by expectations of the unknown.